The Locally Adapted Scaling Vector Method: A New Tool for Quantifying Anisotropic Structures in Bone Images - Monetti, Roberto; Bauer, Jan; Baum, Thomas; Sidorenko, Irina; Müller, Dirk; Eckstein, Felix; Link, Thomas; Räth, Christoph (IntechOpen, 2011)
None